Systematic design of unbonded fiber reinforced elastomeric isolators. (1st February 2017) - Ehsani, Behrang; Toopchi-Nezhad, Hamid
Highlights: Unbonded-FREIs are efficient isolators, however, they introduce few design limitations as they rely on friction to transfer shear and do not take vertical tension. A systematic code-oriented design algorithm that employs equivalent lateral force procedure is provided. The stability of superstructure against sliding and overturning is examined using both the horizontal and vertical components of design earthquake. The nonlinear lateral load-displacement of isolators is addressed in the analysis. The efficiency of the design and stability-check algorithms have been verified using extensive nonlinear time history analyses. Abstract: Fiber reinforced elastomeric isolators (FREIs) comprise alternating bonded layers of elastomer and fiber reinforcement sheets. In an unbonded application the isolator is located in place without any bonding or mechanical fastening provided at its contact supports. The unbonded application results in an increased seismic isolation efficiency, however, it introduces few design limitations as it relies on friction to transfer shear loads, and no vertical tension can be taken by the isolator. These limitations may restrict the use of isolators where the superstructure overturning is of concern or in regions where large vertical ground accelerations are expected. This paper presents a systematic method for the design of structures supported on unbonded-FREIs. The design calculations conform the equivalent static force (ELF) procedure outlined in current seismic codes and account for the vertical component of earthquake in the analysis. A stability parameter has been introduced to verify both the overturning and sliding stability of the isolated system. The efficacy of the design method is illustrated by extensive response history simulations for several prototype frame structures.